Technology readiness of Saudi students and its influence on their intention to use e-learning system. - Azizah Bt Haji Ahm, Osman B Ghazali, Norah Zafer Alduhaim, (Journal of Computing Technologies and Creative Content, 2019)
E-learning systems spreads considerably among educational institution around the world, yet, students’ intention to use them is no in its optimum value. Education institutions in Kingdom of Saudi Arabia invested a lot in installation e-learning system (blackboard), yet, considerable amount of students ineffectively use it. Besides technical aspects of the e-learning system such as ease of use and interactivity, personal dimensions such as Technology readiness may contribute explaining the intention to use among students from negative and positive perspectives. This study tested technology readiness impact on intention of students among students in Saudi capital (Riyadh). 270 respondents’ feedback collected. The findings showed that the negative perspectives of technology readiness (insecurity and discomfort) have insignificant impact compared to positive perspective (optimism and innovativeness).